BIODEGRADASI DODECYL BENZENA SULFONAT DALAM SISTEM LUMPUR AKTIF - I Wayan Budiarsa Suyasa; Ni Putu Diantariani (Bumi Lestari Journal of Environment, 2009)
The research about biodegradation of dodecyl benzene sulfonat ( DBS) has been conducted by using bacterium of sediment of Tebe River in Denpasar. Goals of research were to determine curve of growth bacterium in DBS media and its ability to degradation of DBS. Determination of research consist of exponential phase of bacterium, measurement of volatyl suspended solid (VSS), biologycal oxygen demand (BOD), and biodegradation rate of DBS. Isolate that isolation from Tebe River of Denpasar was seed in DBS media (1g of DBS ;1,5g of NPK ; and 0,2 g of MgSO4.7 H2O to dissolved in 1 L aquadest) with control of growth by measurement of VSS during 12 hours. Active mud that seeding was used to treat of waste water with DBS content. Counted 200 ml active mud in exponential phase, enhanced by 800 ml of waste with DBS content. Measure value of BOD and DBS content, and analysis its rate of decrease. Result of the research indicate that exponential phase of bacterium at an hour of eight with value of VSS equal to 1421,73 mg /l. During treatment of waste, value of BOD and DBS has decreased from initial. Rate of BOD decrease happened to 3 days that following equation is y = - 0,167 X + 3,932 with rate of decrease is 0,167 mg /l. Rate of degradation of DBS quickly, is indicated to 3 days by following fast equation is y = - 0,306X + 6,714 with rate of degrade equal to 0,306 mg /l.